Trends of Physics Education Research on The Topic of Mechanics: A Bibliometric Analysis - Nurjanah, Siti; Supahar, Supahar; Sultan, Jumriani; Fauzan, Muhammad Ikhwan; Sajdah, Siti Nurul; Seran, D'aquinaldo Stefanus Fani; Mwakapemba, James Leonard (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This study aims to map the publication trends of international journal articles related to the topic of mechanics in physics education using bibliometric analysis of the Scopus database. Bibliometric analysis was conducted on the Scopus database with the help of the RStudio application with the biblioshiny package. We analyzed 196 relevant documents filtered with various settings that support the research objectives. The analysis showed a rapid increase in the number of publications on mechanics in physics education since the 2000s (102 articles recorded in 2012–2021), driven by the development of quantitative methods. Physics Education, Physics Teacher, and Revista Brasileira de Ensino de Fisica were the journals with the most contributions. Active author mapping identified Pendrill A-M, Fones SW, and Rieber LP as the most prolific, while citation and h-index analyses showed the work of Rieber LP, Rodrigues H, Adams DM, and Gauld C as the most influential. Geographically, the United States, Brazil, and China dominated publications, with limited international collaboration. This study provided a comprehensive profile of mechanical research trends in physics education to guide future development efforts.